#TITLE_ALTERNATIVE# - Mulyasuryani , Ani
ABSTRACT: The usual method used to determine the phenols content in solution is by spectrophotometry. To do this a reagent is needed, either to form coloured substances with phenols, or to form new substances which are able to absorb at the same wavelength. The aim of this work is to determine phenol directly together with p-nitrophenol and paracetamol, using ultraviolet spectrophotometry. The method is based on the Lambert-Beer law of absorption and additive absorbance properties of several components in solution. The content of each component can be measured using three equations, which can be derived from the Lambert-Beer law. The method gave good results, with a concentration error not higher than 5% . The error may be increased, if there are other ions in the solution which also absorb in the working wavelength region. In this work, the effect of certain ions in solution such as sodium, calcium, iron(1II), nitrate, and sulphate has also been studied. The presence of iron(III) And nitrate in the solution causes an increase of the concentration error.